The ORNAC Legacy Reﬂections on the association's roots with an eye to the future - Donald, Joan (Operating Room Nurses Association of Canada Journal, 1995)
Many operating room nurses are struggling these days to keep up their enthusiasm and faith in our health care system when so many difficult changes are underway in our hospitals.